Habilidades sociales y conductas de riesgo en adolescentes de la Unidad Educativa Fiscomisional “Padre Jorge Abiatar Quevedo Figueroa”, Gonzanamá - Contreras Salinas, Jessica de la Caridad (2023)
The development of social skills in children and adolescents positively impacts the consolidation of identity, as well as in the school, family, and social areas; as they are not enhanced, they lead to unadaptive situations, which cause behavioral difficulties. The purpose of this research was to determine the level of development of social skills, the presence of risk behaviors according to age, sex, and socioeconomic level; and to estimate their correlation in students from 12 to 19 years old from Unidad Educativa Fiscomisional Padre Jorge Abiatar Quevedo Figueroa, in the city of Gonzanamá. A quantitative, cross-sectional study was carried out with a sample of 226 students using the MINSA Social Skills Assessment Test and the adolescent risk behavior questionnaire. Obtaining that 42.9% (n=97) presented a high average in the development level of social skills, with no difference between men and women; while 14.2% (n=32) showed a low level, with a predominance of the middle adolescence group in both sexes. Regarding risk behaviors, 84.51% (n=191) of adolescents do not expose themselves, out of which 45.1% (n=103) are women and 38.9% (n=88) are men. When the variables were related by calculating Chi-square with a value of 95.35, a statistically significant relationship was found with a value of p<0.0. Concluding that the development level of social skills influences the exposure to risk behaviors with an indirect relationship